OPTIMIZING DAYLIGHT USING PASSIVE STRATEGIES: LIGHT SHELVES AND SOLAR TUBES - Nijah Akram; Gohar Nadeem; Dr. Ayesha Mehmood Malik; Fatima Sher; Zain Zulfiqar; Sara Tahir (Spectrum of Engineering Sciences, 2025)
This research investigates how well- advanced daylighting techniques work in atrium buildings, specifically looking at how light shelves and solar tubes can be used together. The importance of daylighting in sustainable building design cannot be overstated, as it provides advantages like better visual comfort, increased occupant health, and lower energy usage. Atrium buildings, featuring spacious central areas, are perfect for integrating these tactics, offering better airflow, more sunlight, and improved spatial connections. The main goal of this study is to boost natural light, decrease dependence on artificial light, and enhance energy efficiency. The performance of these technologies was evaluated through detailed simulations and case studies using advanced daylighting software and real-world assessments. Light shelves raised levels of natural light by 15% to 17% in areas with windows, whereas solar tubes increased brightness from 100 Lux to 200 Lux in areas without windows. Out of the various dimensions examined, 24-inch solar tubes exhibited the greatest uniformity and brightness levels. The combination of light shelves and solar tubes showed noticeable enhancements in visual comfort and energy efficiency, indicating that integrating these daylighting solutions can greatly improve indoor lighting conditions and support sustainable building practices. The results highlight the significance of creative daylighting methods in contemporary architecture, stressing their involvement in establishing healthy, efficient, and productive spaces. This research addresses a significant gap in Pakistan's educational building design by offering simulation-based daylighting solutions customized for local climatic settings and construction techniques. This study offers important information for architects, engineers, and building designers who want to enhance natural lighting and sustainability in built environments.